2014
DOI: 10.1590/1678-775720130689
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment in schoolchildren - a form based on Cariogram® software

Abstract: Identifying caries risk factors is an important measure which contributes to best understanding of the cariogenic profile of the patient. The Cariogram® software provides this analysis, and protocols simplifying the method were suggested.ObjectivesThe aim of this study was to determine whether a newly developed Caries Risk Assessment (CRA) form based on the Cariogram® software could classify schoolchildren according to their caries risk and to evaluate relationships between caries risk and the variables in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Children with a cleft lip and/or palate and non-cleft controls classified in the Cariogram high-risk category had a higher caries experience [ 21 ]. A significant linear regression between mean dmft and caries risk categories assessed according to a form based on the Cariogram was found in children from low-income families ( p < 0.01) [ 22 ]. A statistically significant association between caries experience and Cariogram categories was found ( p < 0.01) in Indian children [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Children with a cleft lip and/or palate and non-cleft controls classified in the Cariogram high-risk category had a higher caries experience [ 21 ]. A significant linear regression between mean dmft and caries risk categories assessed according to a form based on the Cariogram was found in children from low-income families ( p < 0.01) [ 22 ]. A statistically significant association between caries experience and Cariogram categories was found ( p < 0.01) in Indian children [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most used in clinical practice are CAMBRA (Caries Management by Risk Assessment) and Cariogram (complete or excluding data relative to bacterial levels, salivary flow, and buffer potential). The majority of studies regarding children report a significant association between the "high-risk" category, assigned using these models, and the present or future state of caries development [29][30][31]. Nonetheless, the predictive potential of the different models used to evaluate the risk of caries applied to the same population are different, both in longitudinal and cross-sectional studies [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…software has been developed and validated to illustrate graphically the chance of an individual avoiding caries in the near future. 9,10,11,12 Cariogram has been used to predict caries in children, 12 adults 13,14,15,16,17,18,19 and the elderly, 20 and the scientific evidence regarding its prediction efficiency is still questionable. For adults, despite some studies reporting a high predictive value for Cariogram risk levels, 13,18 other studies have not found a correlation between caries experience and any single risk factor proposed by Cariogram.…”
Section: Introductionmentioning
confidence: 99%